Board diversity dan kinerja pasar perusahaan sektor property dan real estate - Dedy Satrio Sejati; Muazaroh Muazaroh (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2024)
This study aims to investigate whether the diversity of board characteristics, such as gender diversity, age diversity, and diversity in length of work, impacts the market performance of companies in the property and real estate sector. The study population comprised 862 companies listed on the Indonesia Stock Exchange (IDX) in 2022. Purposive sampling was employed, and 55 property and real estate companies listed on the Indonesia Stock Exchange (IDX) were selected as the sample during the 2020-2022 period. The study used 163 research data as samples. The results demonstrate that the gender diversity of directors significantly negatively impacts the company's market performance. On the other hand, directors' age diversity significantly impacts the company's market performance. Meanwhile, the directors' service length diversity could be more significant in the company's market performance. The findings of this study suggest that age diversity should be considered when selecting a board of directors in the property sector, as it will complement each other between young and old directors and improve the company's market performance.. Public interest statements The benefit of this research for the general public is understanding the influence of board diversity and the value of property and real estate sector companies as input regarding knowledge for people in the world of work.